Professional SharePoint 2010 cloud-based solutions - Fox, Steven 1970- (Wrox/John Wiley & Sons, 2012)
An authoritative guide to extending SharePoint's power with cloud-based services If you want to be part of the next major shift in the IT industry, you'll want this book. Melding two of the hottest trends in the industry-the widespread popularity of the SharePoint collaboration platform and the rapid rise of cloud computing-this practical guide shows developers how to extend their SharePoint solutions with the cloud's almost limitless capabilities. See how to get started, discover smart ways to leverage cloud data and services through Azure, start incorporating Twitter or LinkedIn int.
Includes bibliographical references and index
Keywords: Microsoft SharePoint (Electronic resource); Intranets (Computer networks); Web servers; Cloud computing; Intranets; Serveurs Web; Infonuagique; intranets; COMPUTERS; Networking; Intranets & Extranets; dissertations; Academic theses; Thèses et écrits académiques